2012
DOI: 10.1371/journal.pone.0036316
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Cytokine Receptors (sIL-2Rα, sIL-2Rβ) Induce Subunit-Specific Behavioral Responses and Accumulate in the Cerebral Cortex and Basal Forebrain

Abstract: Soluble cytokine receptors are normal constituents of body fluids that regulate peripheral cytokine and lymphoid activity. Levels of soluble IL-2 receptors (sIL-2R) are elevated in psychiatric disorders linked with autoimmune processes, including ones in which repetitive stereotypic behaviors and motor disturbances are present. However, there is no evidence that sIL-2Rs (or any peripheral soluble receptor) induce such behavioral changes, or that they localize in relevant brain regions. Here, we determined in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Treatment of pregnant female mice with IL-2 during mid-gestation results in behavioral alterations, including self-grooming and rearing (Ponzio et al, 2007); conversely, IL6 treatment results in decreased PPI (Smith et al, 2007). Furthermore, recent evidence has shown that treatment with specific subunits of the soluble receptors for these cytokines results in stereotyped movements and multiple alterations of locomotor activity (Patel et al, 2012; Zalcman et al, 2012). …”
Section: Animal Models Based On Environmental Etiologymentioning
confidence: 99%
“…Treatment of pregnant female mice with IL-2 during mid-gestation results in behavioral alterations, including self-grooming and rearing (Ponzio et al, 2007); conversely, IL6 treatment results in decreased PPI (Smith et al, 2007). Furthermore, recent evidence has shown that treatment with specific subunits of the soluble receptors for these cytokines results in stereotyped movements and multiple alterations of locomotor activity (Patel et al, 2012; Zalcman et al, 2012). …”
Section: Animal Models Based On Environmental Etiologymentioning
confidence: 99%
“…Another soluble cytokine receptor that is elevated in some autoimmune and neuropsychiatric disorders, sIL-6R, produces effects similar to those observed with sIL-2R (Zalcman et al, 2012) in BALB/c mice (Patel et al, 2012). Vertical stereotypies and novelty-associated exploratory motor behaviors increased within 80 minutes of injection of recombinant human sIL-6Rα, a form that is reactive with both human and mouse IL-6; effects were exacerbated when sIL-6Rα administration was followed by the dopamine uptake inhibitor GBR 12909.…”
Section: Immune-mediated Animal Models Of Tsmentioning
confidence: 83%
“…Soluble cytokine receptors play important roles as regulators of cytokine and lymphocyte activity and are increased in some autoimmune conditions and psychiatric disorders. Balb/c mice receiving single subcutaneous (sc) injections of soluble IL-2 receptors (sIL-2R) α or β showed increased repetitive head bobbing, grooming and rearing/sniffing behaviors as well as other stereotypic behaviors in the vertical and horizontal planes (Zalcman et al, 2012). Effects were most prominent with administration of sIL-2Rβ as compared to sIL-2Rα and behavioral profiles differed slightly for the two sIL-2R subtypes.…”
Section: Immune-mediated Animal Models Of Tsmentioning
confidence: 99%
See 2 more Smart Citations